The cost of additive manufacturing: machine productivity, economies of scale and technology-push - Baumers, Martin; Dickens, Phill; Tuck, Christopher; Hague, Richard (Elsevier, 2016)
As part of the cosmos of digital fabrication technology, Additive Manufacturing (AM) systems are able to manufacture three-dimensional components and products directly from raw material and 3D design data. The layer-by-layer operating process of these systems does not require the use of tools, moulds or dies.